The Role of Institutional Theories in driving CSR agenda amongst MNCs: a Comparative Study of UK and Singapore - Dharmasasmita, Aldilla A. (2014)
This study evaluates the extent to which institutional theories can be drivers and motivations of CSR between the United Kingdom (UK) and Singapore. There currently exist numerous comparative studies analysing countries in a Western context which have similar or different scales of economies, but with relatively similar institutional theories. There have also been several comparative studies published comparing CSR between a developed Western and a developing non-Western context. However less attention has been given comparing developed economies between a Western and non-western context within the one study. For this study, Singapore was chosen as a developed Eastern country and compared with the UK, a Western developed country. Using data analysis from four multi-national companies (MNCs) in the financial sector operating in both UK and Singapore, this research looks at how the theoretical frameworks of the varieties of capitalism, national business system and the institutional theories of each country affect the drivers and motivations of CSR of the financial sector in each country. Through qualitative analysis, the findings in this research support existing literature that varieties of capitalism, national business systems, and institutional theories are major players in effecting CSR motivations at the firm level. Limitations of this research are also highlighted, to pave way for future research in similar context.